Can Machine Translation meet the needs of official language minority communities in Canada? A recipient evaluation - Bowker, Lynne (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Canada is an officially bilingual country, but the only legal requirement is for federal services to be offered in both official languages. Therefore, services provided by provincial and municipal governments are typically offered only in the language of the majority, with cost being cited as the main obstacle to providing translation. This paper presents a recipient evaluation designed to determine whether machine translation could be used as a cost-effective means of increasing translation services in Canadian official language minority communities. The results show that not all communities have the same needs, and that raw or rapidly post-edited MT output is more suitable for information assimilation, while maximally post-edited MT output is a minimum requirement when translation is intended as a means of cultural preservation and promotion. The survey also suggests that average recipients are more receptive to MT than are language professionals.